The Cerpen Burung-Burung Manyar Karya Y.B. Mangunwijaya sebagai Ruang Dialog antara Teks dan Respon Pembaca dalam Resepsi Sastra: Cerpen Burung-Burung Manyar Karya Y.B. Mangunwijaya - Shella Mashita; Meutia Apriliza Ardiani; Muhammad Isman (STKIP Subang, 2025)
This study aims to examine variations in how readers receive the short story “Burung-Burung Manyar” by Y.B. Mangunwijaya and to reveal the process of meaning formation through the interaction between text and reader. The approach used is qualitative with a descriptive analytical method, based on Hans Robert Jauss and Wolfgang Iser's theory of literary reception. The primary data is the text of the short story “Burung-Burung Manyar,” while the secondary data is obtained from in-depth interviews with seven informants. The findings show that readers' reception of this short story varies greatly, influenced by expectations, literacy skills, socio-cultural backgrounds, and the personal experiences of each individual. The dialogue between the text and the reader creates dynamic meaning, confirming that literary texts are open to diverse interpretations. This study makes an important contribution to the study of Indonesian literary reception while confirming the relevance of reception theory in understanding the process of reading contemporary literary works.